On Relationship Between the Resolvent Convergence and the Smoothness of Solutions to Boundary Value Problems - Tsylin, Ivan Vyacheslavovich (Eurasian Mathematical Journal, 2016)
Relationship between the resolvent convergence property and the smoothness of solutions to boundary value problems are studied. The results use pointwise multipliers and \( B \)-spaces.